A2 THE BOWEL CLEANSING NATIONAL INITIATIVE (BCLEAN): PREDICTORS OF INADEQUATE BOWEL PREPARATION - Barkun, A N (J Can Assoc Gastroenterol, 2020)
BACKGROUND: Adequate bowel cleansing before colonoscopy is, in theory, a simple concept but the high rate of inadequate or incomplete bowel cleanliness and its consequences have been the subject of many studies, guidelines, and meta- analyses. The complexity resides in all the pre-endoscopic factors surrounding preparation intake that may? influence quality of the bowel preparation. AIMS: To identify preendoscopic variables associated with inadequate bowel preparation METHODS: In this randomized trial conducted in adult outpatients in 10 Canadian hospitals, all early morning (AM) colonoscopies were scheduled between 7h30AM and 10h30AM and patients were randomized to PEG low volume or high- volume split-dose or high- volume day before. Later colonoscopies (PM) were scheduled between 10h30AM and 16h30PM and patients were randomized to PEG low-volume or high- volume split-dose or low- volume same day. A secondary random allocation assigned patients to a clear fluid or low residue diet. Inadequate bowel preparation was identified on the Boston Bowel Preparation Scale with a total score <6 with any of the 3 colonic segments subscores <2). All preendoscopic variables such as patients related factors, diet and type of bowel preparation were evaluated between groups with chi-square, Fisher’s exact or t-test where appropriate. All variables found to be significantly associated with a clean preparation on univariable analysis at the P=0.15 level were used to construct a multivariable model. Because of stratified randomization by time with possible resulting differing confounders, AM and PM patients were analysed separately. RESULTS: Over 29 months, 1726 patients were stratified in the AM group and 1750 patients in the PM group. 16.9% had inadequate bowel preparation in the AM group and 9.8% in the PM group. Pre-endoscopic variables associated with an inadequate bowel cleanliness in AM colonoscopy were a non screening indication (OR 1.36, 95%CI 1.04–1.78), a Charlson score>0 (OR 1.36, 95% 1.03–1.80) and a low residue diet (OR 1.53, 95%CI 1.17–2.01). Amongst PM colonoscopies, variables associated with an inadequate bowel cleanliness were increased age (OR 1.03, 95% 1.01–1.04), a non screening indication (OR 1.90 95%CI 1.35–2.70); a Charlson score>0 (OR 1.63, 95%CI 1.15–2.32), and a low residue diet (OR 1.41, 95%CI 1.01; 1.98). CONCLUSIONS: In this large randomized trial, amongst patients undergoing an AM colonoscopy, pre- endoscopic factors associated with an inadequate bowel preparation were a non screening indication, comorbidities and a low residue diet. Amongst PM colonoscopy patients, in addition to these variables, an increased age was also associated with an inadequate bowel preparation. FUNDING AGENCIES: received arm-length funding from Pendopharm Inc.